MODEL KONSEPTUAL PENINGKATAN KUALITAS LAYANAN INDUSTRI PARIWISATA DI JAWA TENGAH MENGGUNAKAN TOURSERVQUAL - Marlyana, Novi; Khoiriyah, Nuzulia (Jurnal Kawistara, 2015)
Several previous studies have found factors or dimensions that affect the quality services of tourism and measures the perceived level of tourists as consumers. However, these studies have not been able to develop a practical model of a system as a simple overview of the tourism industry by involving various factors / dimensions that influence. This research will make a conseptual model of the service quality improvement of the tourism industry in the province of Central Java. The method used in this paper is Tourservqual, which is the Service Quality methods applied in the field of tourism. The resulting conceptual model consists of sixteen (16) dimension of the quality of tourism services that will affect or have a positive relationship with customer satisfaction (tourists). Customer satisfaction has a positive influence on destination competitiveness. Destination competitiveness measured in 36 indicators. This conceptual model expected to measure tourist satisfaction who becomes the object of the tourist areas, also measure the level of competitiveness of each of these objects, as well as knowing what factors most affect the competitiveness of tourist destinations.